Various memories of Rumen Maleev - the colleague and friend (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2020)
This is Stanimir Troyanski's personal account of the late Professor Rumen Maleev.The author shares his reminescences about his dear friend and colleague.